(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Historically researched international legal protection of intellectual property. The experience of the protection of intellectual property rights in the USA, Japan and the European Union was studied. The article describes the influence exerted by international organizations and foreign countries on Russian legislation, which provides for the application of measures to protect intellectual property.